Telemedicine as a tool for bridging geographical inequity: insights in geospatial interactions from a study on chronic heart failure patients - Alexander Arndt Pasgaard Xylander; Simon Lebech Cichosz; Ole Hejlesen; Flemming Witt Udsen (BMC, 2024)
Abstract Introduction Chronic heart failure patients experience large disparities in quality of and access to treatment, with rural populations receiving lower levels of care. Telemonitoring of patients is increasingly being used as an important tool for improving patient management and care and might reduce geographical inequities in healthcare. Methods We investigate the presence and magnitude of a geospatial interaction effect on the health benefit of a supplementary telemedicine intervention, by analyzing the relationship between distance to regular place of treatment and the benefit of telemedicine in a secondary analysis of data from a previously conducted RCT. We use change in EQ5D health status, SF-36 Physical component score and SF-36 Mental component score as the outcomes. In the unadjusted analysis, intervention group and distance group and the interaction term are included as the independent variables, in the adjusted analysis, multiple socioeconomic and health related variables are included to account for potential confounders. Results We find evidence of a significant interaction between the effects of telemedicine and long distance to treatment for change in EQ5D health status (unadjusted: p = 0.016, adjusted p = 0.009) and unadjusted but not adjusted mental component score (unadjusted: p = 0.013, adjusted p = 0.0728), for the change in physical component score the interaction term was not significant (unadjusted: p = 0.118, adjusted p = 0.092). Conclusion In our study we find that supplementary telemedicine is likely to reduce the health access inequities associated with geographical distance for chronic heart failure patients. However, our sample size was modest and further research is needed to confirm these findings.